2009
DOI: 10.1001/archdermatol.2009.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Physician Discovery of Early Melanoma in Middle-aged and Older Men

Abstract: Objective:To determine factors associated with physician discovery of early melanoma in middle-aged and older men. Design: Survey.Setting: Three institutional melanoma clinics.Participants: A total of 227 male participants (aged Ն40 years) with invasive melanoma who completed surveys within 3 months of diagnosis.Intervention: Survey. Main Outcome Measures: Factors associated with physician-detected thin melanoma.Results: Patients with physician-detected melanoma were older, 57% were 65 years or older compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
1
3

Year Published

2009
2009
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 17 publications
(20 reference statements)
8
28
1
3
Order By: Relevance
“…Another potential explanation is that patients who examine more body sites may not be focusing on areas where melanomas are more likely to occur, that is, back of the body. Physicians also play a role in examining body sites that are harder for patients to see (25).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation is that patients who examine more body sites may not be focusing on areas where melanomas are more likely to occur, that is, back of the body. Physicians also play a role in examining body sites that are harder for patients to see (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all of the studies have found a favorable tumor thickness for melanoma diagnosed by primary care providers at least 0.5 to 1.00 mm thinner. 36,37 In a study of cases diagnosed in Michigan and California, 69% of physician-diagnosed melanomas were less than 1 mm compared with 33% of self-detected melanomas. 36 However, less than half of US physicians routinely examine the skin for cancer, and neither medical students nor primary care residents are adequately trained in skin cancer examination.…”
Section: Clinician Educationmentioning
confidence: 99%
“…36,37 In a study of cases diagnosed in Michigan and California, 69% of physician-diagnosed melanomas were less than 1 mm compared with 33% of self-detected melanomas. 36 However, less than half of US physicians routinely examine the skin for cancer, and neither medical students nor primary care residents are adequately trained in skin cancer examination. [38][39][40][41] Much remains unknown about melanoma discovery patterns and differences between dermatologist and primary care provider biopsy and referral practices.…”
Section: Clinician Educationmentioning
confidence: 99%
“…Middle-aged and older men are recognized as a high-risk group 29 , probably due to low prediagnosis awareness of melanoma warning signs and poor skin self-examination practices 30 . In Latin America there are also elevated incidence rates of invasive melanoma among males in older age-groups (60 or more), perhaps associated with age-associated changes in the immune system, lower socioeconomic groups and late diagnosis due to a relative lack of access to medical care 29,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America there are also elevated incidence rates of invasive melanoma among males in older age-groups (60 or more), perhaps associated with age-associated changes in the immune system, lower socioeconomic groups and late diagnosis due to a relative lack of access to medical care 29,30,31 .…”
Section: Discussionmentioning
confidence: 99%